Tradition and Transitions: Elders Working in Canadian Prisons, 1967-1992 - Adema, Seth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2014)
Between 1967 and 1992, Aboriginal traditional Elders played increasingly important roles working with Aboriginal inmates in Canadian penitentiaries. Whereas in 1967 a small group of individuals entered prisons as Elders on a voluntary basis, unrecognized by Correctional Services Canada (CSC), over the following decades Elders and CSC developed increasingly formal relationships. By 1992 the Corrections and Conditional Release Act legislated the employment of Elders as spiritual leaders for Aboriginal peoples in prison. This transition was brought about because of an ongoing cultural dialogue between Aboriginal prisoners through inmate groups called the Native Brotherhoods, Aboriginal community organizations that worked inside prisons, and penal administrators. While Native Brotherhoods and the Elders who worked with them were central to the decolonization of prisons, in legislating the practice of Aboriginal spirituality in prisons and mandating the employment of Elders, CSC took control of Aboriginal cultural practices and alienated the community groups that once supported Elders. While the increased rights of Elders under this new framework responded to many of the needs voiced by prisoners and community members, the shift from community-based to institutional-based service represented an important change in the relationship between Aboriginal peoples and Canadian penal institutions. This paper argues that the efforts of individual Elders and Native Brotherhoods and the consolidation of control over their efforts by the penal administrations were the result of simultaneous processes of decolonization and neocolonialism.